Markets of agro-industrial complex products in conditions of geoeconomic fragmentation of the international trade - E. N. Smirnov; E. A. Karelina; M. G. Pletnev (Вестник университета)
For decades, international trade has contributed to the reduction of global poverty and the income gap between countries, and the development of intercountry exchange of agricultural products has largely ensured the solution of problems of poverty and food security. At the same time, at the present stage, a high degree of dependence of many developing countries on food imports has occured, while its global exporters have faced a number of restrictions on the supply of their agricultural products. This article analyses the impact of geoeconomic fragmentation of the international trade on the development of exports and imports of products of the agro-industrial complex (hereinafter referred to as AIC). In particular, the problems of competition in the world agro-food markets are discussed in a new context, since the growing problems of monopolisation in certain segments of the AIC disrupt the stability of agricultural markets. Exclusive attention is paid to the key aspects of the application of non-tariff measures in regulating trade of the agricultural products, which, in addition to the protective role, can have a distorting effect on world prices. Our analysis places particular emphasis on the hidden costs of global agri-food systems, which necessitate their rapid modernisation to ensure sustainability in the development of the agricultural markets and to address global food security issues.